Hubungan antara Dukungan Sosial Dengan Stres pada Narapidana NAPZA di Lembaga Pemasyarakatan Narkotika Yogyakarta - Tri Pujl Astuti; Titik Kuntari; Sufi Desrini (Faculty of Medicine, Universitas Islam Indonesia, 2009)
Drug abuse (Narcotics, psychotropics, and addictives) as social illness is harmful to various aspects of human life such as health, education, security, and social economy, and this is a serious threat to Indonesia as a big nation. Drug abuse has strong relationship with str ss triggered by stressor. Some researches report that to prevent stress, social support is one of important sources applied beside constitution, intelligence, financial resources, faith and religion, hobbies and aspirations. The objective of this study is to determine the relationship between social support and stress among drug abuse inmates in Yogyakarta Narcotics Penitentiary. We used descriptive analysis with cross sectional method. This correlational study was conducted in Yogyakarta Narcotics Penitentiary with 52 subjects using stress scale and Social Support Questionnaire. Analysis on correlation using Kendall Tau formula. 51,9% of total respondent had medium stress level and 57,7% had very high social support level. Statistical test found significant relationship between stress with social support ( P-value = 0.002, t = -0 .328) and duration of drug abuse (P-value = 0.015, t = 0.312). There is significant relationship between social support and stress among drug abuse inmates in Yogyakarta Narcotics Penitentiary.